Sosialisasi Pengenalan Alat Dan Pengecekan pH Tanah Untuk Hasil Panen - Fatikhatun Nikmatus Sholihah; Suci Prihatiningtyas; Eldy Zakkirul; Ahmad Iqbal Hidayatulloh; Maya Tri Maula (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2026)
The majority of the population in Kedungpapar village work as farmers, as evidenced by the large amount of agricultural land available, but these rice fields have not been optimally utilized, as evidenced by production results that do not meet planned targets. One factor contributing to suboptimal rice or corn harvests is that the soil used has a pH that differs significantly from the optimum pH, which tends to be significantly different, making the fertilizer applied difficult for plants to absorb, thus disrupting plant growth. Therefore, researchers created a smartphone-based nutrient detector that can be accessed anytime and anywhere. The approach method for implementing community service activities in the KKN-PPM program uses a community-based research method, namely explanations from resource persons to partners. Through socialization and direct practice in the field, farmers gain new knowledge about the importance of soil pH, how to use digital pH measuring instruments, and steps to handle if the soil pH is not appropriate. This activity is expected to improve harvest quality, fertilizer use efficiency, and farmer welfare in a sustainable manner